Synthesis and electrochemical characterizations of (poly3,4 ethylenedioxythiophene/manganese oxide coated on porous carbon nanofibers as a potential anode for lithium-ion batteries - Mohd Abdah, Muhammad Amirul Aizat; Mokhtar, Marliyana; Lee, Tian Khoon; Sopian, Kamaruzzaman; Dzulkurnain, Nurul Akmaliah; Ahmad, Azizan; Sulaiman, Yusran; Bella, Federico; Su’ait, Mohd Sukor (Elsevier BV, 2021)
Poly(3,4-ethylenedioxythiophene)/manganese oxide coated on porous carbon nanofibers (P-CNFs/PEDOT/MnO2) is developed as an advanced anode material via the innovative combination of multiple routes, such as electrospinning, carbonization and electrodeposition. The structural and morphological characterization of the P-CNFs/PEDOT/MnO2 electrode indicates that crosslinked and rough surface provides, as a strategic point, enough active sites for Li+ storage. PEDOT nanoparticles and irregular block shape of MnO2 are randomly oriented on the P-CNFs surface, thus allowing a possible electron-conducting pathway, increment in catalytic activity as well as a buffer of the volumetric changes upon cycling. Consequently, the obtained P-CNFs/PEDOT/MnO2 electrode exhibits a truly promising electrochemical performance, which displays discharge capacity of 1477 mAh/g, better than that of P-CNFs/PEDOT (1191 mAh/g), P-CNFs/MnO2 (763 mAh/g) and P-CNFs (433 mAh/g), at a current density of 2 mA/g. In addition, satisfactory electrochemical performances of the as-prepared P-CNFs/PEDOT/MnO2 electrode after 20 cycles of charge/discharge are detected, with a Coulombic efficiency higher than 90% and a charge-transfer resistance being relatively smaller (131.91) than that of P-CNFs/PEDOT (232.66) and P-CNFs/MnO2(169.17) electrodes. Thus, these results indicate that the P-CNFs/PEDOT/MnO2 electrode could offer a great potential to replace commercial graphite for lithium-ion batteries.